The Effect of Family Socialization, Teacher Example, and Heterogeneity Society Towards Global Diversity Character of Five Principles Students Profile - Yeni Susanti (Universitas Negeri Semarang, 2024)
This inquiry looks at the impact of family socialization, educator illustration, and heterogeneity of society towards worldwide differences in the character of the five standards understudies profile of State Islamic Senior Tall School 2 Surakarta. This investigation is inquired about with a quantitative approach, employing a study strategy with an informative inquiry about sorts. The comes about of this investigation shows that the factors tried appear in a tall category, specifically the concentrated of the family socialization variable is 98,8%, the level of the commendable educator is 91.6%, social heterogeneity is 81,9% and the level of the worldwide differences of character is 92.8%. Based on the results of the t-test, appears that there’s a noteworthy impact between the three subordinate factors on the free factors with an importance of less than 0.05 and the comes about of the F-test appears that the speculation is acknowledged with a likelihood of less than 0.05, as well as the comes about of testing the coefficient of assurance (R2) gotten a Balanced R Square esteem of 0.224, meaning that the concentrated of family socialization, the level of model educator, and social heterogeneity can impact the level of worldwide differences of character by 22.4%. The hypothetical suggestion in this inquiry is the reasonableness between the comes about of information examination and George Herbert Mead’s Socialization Hypothesis (1972), Jean Baudrillard’s Simulacra and Recreations Hypothesis (1985), Albert Bandura’s Impersonation Hypothesis (1977), and Pierre Bourdieu’s (1986) Social Capital Hypothesis. Globalization Thomas Larsson Friedman (2001).